Implementasi Kebijakan Penyaluran Dana Desa Dalam Pengelolaan Bumdes di Desa Pandan Landung dan Desa Jedong Kecamatan Wagir - Fransiska Noviana; Cahyo Sasmito; Asih Widi Lestari (Universitas Serang Raya, 2023)
The purpose of this study was to find out how the implementation of channeling village funds in the management of BUMDes in Pandan Landung Village and Jedong Village, Wagir District, Malang Regency, to find out and examine the variables that can help and hinder the implementation of village fund distribution in the management of village-owned enterprises. Methods of collecting information using descriptive qualitative with observation, interviews, and documentation. The results of the study found that BUMDes policies in Pandan Landung Village and Jedong Village could be implemented effectively based on the Van Meter Van Horn policy implementation model. Policy size and objectives, capital resources, inter-organizational communication, social conditions, and human resources are supporting factors for implementing BUMDES management of village fund distribution in Pandan Landung Village and Jedong Village. Barriers to the implementation of BUMDes management, such as firstly the lack of socialization of the Village government to the community, secondly there is still an apathetic community, thirdly the lack of adequate time and human resources that need to be added so that they can run effectively due to one another's busyness and lack of finance and natural resources in two village.